Video Streaming over WLANs with QoS support - Zhang, Yu (2009)
With the deployment of wireless local area networks (WLANs), a low cost WLAN adaptor provides users with a convenient access to the Internet in any area with a WLAN access point (AP). Furthermore, with the QoS extension of the WLAN, it becomes an efficient and practical wireless access platform with QoS support for various applications. Among the applications, video streaming is one of the most attractive applications for WLANs. However, due to the characteristics of wireless communications such as high error rate, limited bandwidth, time-varying channel conditions and dynamic network users, wireless video streaming faces many challenges. A framework should be employed to link the QoS facilities supported by the WLAN with the video applications. This thesis deals with the issue of the video streaming over WLANs with QoS support.